PREVENTION OF VIOLENCE AGAINST WOMEN IN DISADVANTAGED FAMILIES - Sultanova, Natalia; Lemko, Halyna; Voroshchuk, Oksana (Mountain School of Ukrainian Carpaty, 2023)
In the article, the authors determined the relevance of the problem of violence against women and its prevention in dysfunctional families; the ways of social assistance to them and prevention of complications of the consequences of violence in the family are revealed. The content of the definition of "disadvantage" of the family and its status, which is revealed due to the connection with the specific situation of the functioning of the family and its individual members, have been clarified. The authors also characterized the phenomenon of violence against women in terms of physical, psychological, sexual and economic content. The content of the root causes of violence is revealed and revealed from the point of view of a retrospective review of the problem and taking into account the opinions of supporters of psychological theories and theories of social causation. The causes of family dysfunction are listed, such as economic instability, unemployment, legal illiteracy, alcohol and drug addiction of family members, lack of understanding of life goals and means of achieving them, and their impact on the risk and perpetration of violence against women in dysfunctional families is substantiated. . Emphasis is placed on the multiplicity of root causes of violence and their conditioning by a set of interrelated factors and factors. The possibility of influence of some on the crucial importance of others in dysfunctional families has been proven. The need for specialists in the field of social work, social pedagogues, and psychologists to provide qualified assistance to women who have become victims of domestic violence is substantiated. Social protection of women, in particular in dysfunctional families, is presented in the article as a holistic system of social prevention, which is based on clearly formulated principles and legal acts. The possibilities and expediency of social prevention of violence against women in dysfunctional families are substantiated; revealed the content and purpose of its three levels: primary, secondary, tertiary. Resources for the development and improvement of preventive activities to prevent violence against women in dysfunctional families are outlined. It was concluded that the effectiveness of social work with women who have become or could potentially become victims of violence will be facilitated by a set of preventive measures to prevent men's cruel treatment of them, and directions of work to overcome the consequences of domestic violence against them in dysfunctional families.